Expressions of Mental Disorder in the Qur'an: An Analysis of QS. Yūsuf [12]: 13 and 84 Using of Ma'nā-cum-Maghzā Approach - Erina Aolia; Abdul Gaffar; Danial Danial; Ros Mayasari (Pappaseng: International Journal of Islamic Literacy and Society, 2025)
This study is based on the reality that mental disorders continue to be misunderstood in society, despite their serious impacts on an individual's psychological and physical health. This study aims to examine QS. Yūsuf [12]:13 and 84 within the conceptual framework of mental disorders, focusing on the emotional story of Prophet Ya’qub that depicts deep sadness and worry, which affected his physical condition. The method used is the Ma’nā-cum-Maghzā hermeneutical approach to explore the meanings of key terms in the verses and their relevance to modern psychological phenomena. The results of the analysis indicate that terms such as ḥuzn, khawf, asafā, and kaẓīm not only contain spiritual meanings but also imply psychosomatic symptoms consistent with the concept of mental disorders, such as depression and anxiety. This study contributes theoretically to the development of multidisciplinary thematic exegesis and has practical implications for the development of therapy based on Qur’anic values. These findings highlight the need for integration between exegetical approaches, psychology, and Islamic spirituality in addressing the psychological challenges faced by the Muslim community in the modern era.